Impact of immune-related adverse events on treatment outcomes in advanced esophageal squamous cell carcinoma treated with immune checkpoint inhibitors - Zhang, Tianhang; Chen, Xiao; Wu, Jianhua; Li, Jiasong; Qin, Zhukun; Cao, Ruijie; Guo, Wei; Guo, Zhanjun; Fan, Haiyan (Frontiers in Immunology, 2026)
BackgroundWhile immune-related adverse events (irAEs) are associated with better prognosis in advanced esophageal squamous cell carcinoma (ESCC), the prognostic impact of single-organ irAE (uni-irAE), multiple-organ irAEs (multi-irAEs), and organ-specific irAEs remains poorly understood. This study aimed to address this gap by evaluating the effects of various irAEs on survival and characterizing the co-occurrence patterns of multi-irAEs in ESCC patients.MethodsWe retrospectively analyzed 213 ESCC patients treated with immune checkpoint inhibitor (ICI), dividing them into non-irAE, uni-irAE, and multi-irAEs groups to compare their efficacy and prognosis. Baseline characteristics and efficacy outcomes were compared by Chi-square test. Prognostic analysis was performed using Kaplan-Meier survival analysis with the log-rank test and Cox proportional hazard models. The Mann-Whitney U test was used to compare the time to onset of irAEs. Additionally, logistic regression analysis was conducted to identify risk factors associated with the development of multi-irAEs.ResultsPatients who developed irAEs exhibited a significantly higher disease control rate (DCR) compared to patients without irAEs (94.9% vs. 82.1%, p = 0.007). This was observed in both the uni-irAE group (93.4% vs 82.1%, p = 0.036) and as a trend in the multi-irAEs group (100% vs. 82.1%, p = 0.078) when compared to the non-irAE group. Multivariate analysis revealed that the development of uni-irAE was an independent protective factor for both progression-free survival (PFS; hazard ratio [HR] 0.57, 95% confidence interval [CI] 0.39-0.83, p = 0.003) and overall survival (OS; HR 0.64, 95% CI 0.44-0.95, p = 0.028). Similarly, multi-irAEs were identified as an independent protective factor for OS (HR 0.41, 95% CI 0.20-0.86, p = 0.019). Analysis of co-occurrence patterns showed that endocrine irAEs were frequently leading to multi-irAEs. Furthermore, a multivariate Cox regression confirmed that endocrine irAEs and mild (grade 2 or lower) irAEs were independently associated with favorable survival outcomes.ConclusionThe occurrence of both uni-irAE and multi-irAEs was associated with favorable prognosis in ESCC patients treated with ICIs. Furthermore, patients who developed endocrine irAEs or mild irAEs also demonstrated improved efficacy, suggesting their potential as clinical response markers for a positive response to therapy. This finding emphasizes the necessity of vigilant monitoring and early intervention for irAEs in patients undergoing ICIs.